Assessing outcomes for cost-utility analysis in depression: comparison of five multi-attribute utility instruments with two depression-specific outcome measures. (November 2014) - Mihalopoulos, Cathrine; Chen, Gang; Iezzi, Angelo; Khan, Munir A.; Richardson, Jeffrey
Abstract : Background: Many mental health surveys and clinical studies do not include a multi-attribute utility instrument (MAUI) that produces quality-adjusted life-years (QALYs). There is also some question about the sensitivity of the existing utility instruments to mental health. Aims: To compare the sensitivity of five commonly used MAUIs (Assessment of Quality of Life – Eight Dimension Scale (AQoL-8D), EuroQoL–five dimension (EQ-5D-5L), Short Form 6D (SF-6D), Health Utilities Index Mark 3 (HUI3), 15D) with that of disease-specific depression outcome measures (Depression Anxiety Stress Scales (DASS-21) and the Kessler Psychological Distress Scale (K10)) and develop 'crosswalk' transformation algorithms between the measures. Method: Individual data from 917 people with self-report depression collected as part of the International Multi-Instrument Comparison Survey. Results: All the MAUIs discriminated between the levels of severity measured by the K10 and the DASS-21. The AQoL-8D had the highest correlation with the disease-specific measures and the best goodness-of-fit transformation properties. Conclusions: The algorithms developed in this study can be used to determine cost-effectiveness of services or interventions where utility measures are not collected.